Effectiveness of Singapore's procreation and marriage incentives. - Koh, Adrian Yong Chun. (2008)
The recent decline in birth rate has been a glaring issue due to its serious repercussions on the economy. The resulting ageing population will cause an increase in the old-age dependency ratio and labour shortage which will adversely affect Singapore’s economy. As such, the Singapore Government has implemented numerous procreation and marriage incentives in Budget 2004. Together with the existing incentives, they purport to curtail the problem on hand.